Outcome Statement: Adaptation of African Agriculture: From Science to Action - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2016)
The “Adaptation of African Agriculture: from science to action” event held on 13 November 2016, focused on the implementation of the Adaptation of African Agriculture initiative ("AAA"), launched by the Moroccan Government to transform African Agriculture. This outcome statement summarises the cross cutting priorities for action which emerged during the discussion, and highlights event outcomes.